Healthcare technology management : a systematic approach - Hegarty, Francis; Amoore, John N.; Blackett, Paul; McCarthy, Justin (Clinical engineer); Scott, Richard, 1962- (CRC Press, Taylor & Francis Group, 2016)
"This book offers a comprehensive approach for providing cost effective healthcare technology management (HTM) at the lowest risk. The authors propose a management model based on two interlocking quality cycles which, when fully implemented, delivers a comprehensive and transparent model for implementing an HTM program throughout an institution. The book shows how to cost effectively manage the resources of medical equipment through its full lifecycle, from acquisition through operational use, to disposal, supporting better healthcare at lower costs"- Resumé vydavatel